On the validity of difusional model in determination of electric transport parameters of semiconductor compound (2014)
In this work we have studied the variable range hopping as a predominant electronic transport mechanism for semiconductor materials used as absorbent layer in photovoltaic devices. Dark conductivity measurements were carried out from 120 to 420 K in Si, Cu3BiS3, SnS, Cu2ZnSnSe4, and CuInGaSe2 thin lms. In the low-temperature range, variational range hopping was established for all samples. Using classical equations from the percolation theory and the difusional model, the density of states near the Fermi level (NF), as well as the hopping parameters (W-activation energy and R hopping range) were calculated. A correlation between both models allowed us to evaluate the validity of the difusional model in semiconductor compounds.